POSITIVE-SELF AND NEGATIVE OTHER PRESENTATION IN THE 2016 U.S. PRESIDENTIAL ANNOUNCEMENT SPEECHES: A CRITICAL DISCOURSE ANALYSIS - Rinaldo, Zainal Arifin (TELL - US JOURNAL, 2016)
The aim of this research is to investigate the ideology manifestation of each political party (Republican and Democratic) with respect to the current issue of social, economy, politics, education, and foreign policy of the U.S. through the analysis of positive-self and negative-other presentation in the announcement speeches delivered by the candidates who run for the 2016 U.S. Presidential bid. Besides, this study also aims at investigating how the candidates from each party try to justify themselves and persuade the audience to win their consensus. The four candidates whose speeches being analyzed are Hillary Rodham Clinton, Bernie Sanders, Donald Trump, and Ben Carson. The research was conducted under the theory of Critical Discourse Analysis (CDA) proposed by Dijk and Wodak. The result shows that the positive-self and negative-other presentation performed by the candidates through p r e d i c a t i o n a l , r e f e r e n t i a l / n o m i n a t i o n , a r g u m e n t a t i o n , p e r s p e c t i v a t i o n , and i n t e n s i f y i n g s t r a t e g i e s . The presence of positive-self and negative-other presentation indicate that the manifestation of ideology in political speech is possible to be delivered through implicit assumptions and evaluative attributions.